PENGARUH LUAS PENGUNGKAPAN SOSIAL DALAM LAPORAN TAHUNAN TERHADAP REAKSI INVESTOR DAN KINERJA PERUSAHAAN HIGH PROFILE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hermi Hermi; Lydia Desvita Sari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
The purpose of this research is to know the influence of social disclosure on annual report toward investor reaction and corporate performance on high profile companies is listed Indonesia Stock Exchange. Fourty two are registered companies were used as research sample which consist of 42 high profile companies those are listed Indonesia Stock Exchange for 2006-2007. So that, this research uses 84 high profile companies as observation. These samples were selected by using purposive sampling method. Analysis hypothesis is using Regression, and normality data test using One-Sample Kolmogorov-Smirnov Test. The result concluded by using Regression is that investor reaction which measures with unexpected trading volume is not influenced by social disclosure. Beside that, this social disclosure is also not giving influence toward corporate performance which measured by Assets Turnover. But social disclosure influences the corporate performance which measured by Return on Equity.